(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
Drug actions can be improved by developing new drug delivery systems, such as the mucoadhesive system. These systems remain in close contact with the absorption tissue, the mucous membrane, releasing the drug at the action site leading to a bioavailability increase and both local and systemic effects. Mucoadhesion is currently explained by six theories: electronic, adsorption, wettability, diffusion, fracture and mechanical. Several in vitro and in vivo methodologies are proposed for studying its mechanisms. However, mucoadhesion is not yet well understood. The aim of this study was to review the mechanisms and theories involved in mucoadhesion, as well as to describe the most-used methodologies and polymers in mucoadhesive drug delivery systems.